Performance evaluation of paddy seed distribution using cylindrical seed container spreader robot - Azahar, Arman Hadi; Harun, Mohamad Haniff; Mohd Zabidi, Muhammad Izzat Zakwan; Md Johari, Md Ashadi; Azahar, Adila Aida; Sha'abani, Mohd Nurul Al Hafiz (Wydawnictwo SIGMA-NOT, 2024)
Agriculture is evolving in lockstep with technological advancements. Agricultural activities are facilitated by its development. This paddy planter is utilised in paddy farming where paddy seeds are employed. Rice cultivation has historically impacted cultivation lengths, resulting in an excess of used paddy seeds, and cultivation processing has historically consumed the majority of manpower requirements. As a result, increased emphasis should be placed on automating these procedures in order to reduce manpower requirements in rice cultivation and hence improve profitability, and There are numerous dangers associated with conventional rice production. The purpose of this project is to address this issue. Additionally, this project reduces the leasing cost of the existing machine, which has a significant maintenance cost. This robot is controlled by a remote control. When the engine is driven by a paddy storage container and the tyres are concurrently moved, the paddy seeds will fall out of the storage container.